A bioinspired 3D shape olibanum‐collagen‐gelatin scaffolds with tunable porous microstructure for efficient neural tissue regeneration. (16th October 2019) - Ghorbani, Farnaz; Zamanian, Ali; Kermanian, Fatemeh; Shamoosi, Atefeh
Abstract: There are a number of procedures for regeneration of injured nerves; however, tissue engineering scaffolds seems to be a promising approach for recovery of the functionality of the injured nerves. Consequently, in this study, olibanum‐collagen‐gelatin scaffolds were fabricated by freeze‐cast technology. For this purpose, the olibanum and collagen were extracted from natural sources. The effect of solidification gradient on microstructure and properties of scaffolds was investigated. Scanning electron microscopy micrographs showed the formation of lamellar‐type microstructure in which the average pore size reduced with an increase in freezing rate. According to the results, the prepared scaffolds at lower freezing rate showed a slight reduction in mechanical strength while the swelling and biodegradation ratio were increased due to the presence of larger pores and unidirectional channels. The composition of scaffolds and oriented microstructure improved cellular interaction. In addition, scaffolds with lower freezing rate exhibited promising results in terms of adhesion, spreading, and proliferation. In brief, the synthesized scaffolds at lower solidification rate have the potential for more in vitro and in vivo analyses to regeneration of neural defects.